2018
DOI: 10.1536/ihj.16-625
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuous Administration of Tolvaptan on Preventing Medium-Term Worsening Renal Function and Long-Term Adverse Events in Heart Failure Patients with Chronic Kidney Disease

Abstract: SummaryTolvaptan (TLV) has an inhibiting effect for worsening renal function (WRF) in acute decompensated heart failure (HF) patients. However, there are limited data regarding the effect of continuous TLV administration on medium-term WRF.This was a retrospective observational study in hospitalized HF patients with chronic kidney disease (CKD). TLV was administered to those patients with fluid retention despite standard HF therapy. We compared 34 patients treated with TLV (TLV group) to 33 patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…The primary endpoint of this study was rehospitalization due to worsening HF, and the secondary endpoints Kaplan-Meier analysis revealed that the incidence of rehospitalization was significantly lower in the TLV (+) group than in the TLV (−) group (log-rank test; p = 0.018) ( Figure 2). As shown in 18,19 In our study, 82.8% of the patients started TLV therapy from the first day of hospitalization, and TLV therapy reduced loop diuretics doses both at discharge and after 6 months, and it also prevented WRF development until 6 months…”
Section: Echocardiographysupporting
confidence: 68%
“…The primary endpoint of this study was rehospitalization due to worsening HF, and the secondary endpoints Kaplan-Meier analysis revealed that the incidence of rehospitalization was significantly lower in the TLV (+) group than in the TLV (−) group (log-rank test; p = 0.018) ( Figure 2). As shown in 18,19 In our study, 82.8% of the patients started TLV therapy from the first day of hospitalization, and TLV therapy reduced loop diuretics doses both at discharge and after 6 months, and it also prevented WRF development until 6 months…”
Section: Echocardiographysupporting
confidence: 68%
“…Major depression is a common comorbidity in patients with heart failure [30][31][32] and results in poor quality of life, an increased risk for hospitalization, and mortality. [33][34][35][36][37][38][39] A vast majority of heart failure patients have symptoms of depression and anxiety. 3) Depressive symptoms show a strong negative impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…_ 1 ) T D $ F I G ] renal function is a key to better prognosis in HF patients. Table 2 summarizes the results of six long-term tolvaptan therapy studies, including four Japanese ones [27,[31][32][33][34]. Tolvaptan dose ranges were 4.9-9.8 mg/day in four Japanese studies, whereas two studies in other countries were performed at 30 mg/day [20,35].…”
Section: Renal Functionmentioning
confidence: 99%